Correction: Hydrogel networks as underwater contact adhesives for different surfaces. Issue 8 (22nd July 2020) - Feng, Pan; Ye, Shaoxiong; Wang, Ruixing; She, Wei; Liu, Jiaping; Sun, ZhengMing; Zhang, Wei
Abstract : Correction for 'Hydrogel networks as underwater contact adhesives for different surfaces' by Pan Feng et al ., Mater. Horiz., 2020, DOI: ; 10.1039/d0mh00176g .